1996
DOI: 10.1002/(sici)1096-8628(19960202)61:4<329::aid-ajmg6>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Fetal alcohol syndrome: Craniofacial and central nervous system manifestations

Abstract: Magnetic resonance imaging (MRI) is undertaken on fetal alcohol syndrome (FAS) subjects to document central nervous system (CNS) anomalies. The abnormalities found include agenesis and hypoplasia of the corpus callosum, cavum septi pellucidi, cavum vergae, ventriculomegaly, hypoplasia of inferior olivary eminences, small brain stem, and micrencephaly. Craniofacial anomalies range from the well‐recognized FAS physiognomy to the more severe frontonasal “dysplasia” (median cleft face). CNS and craniofacial abnorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
1
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(57 citation statements)
references
References 32 publications
2
53
1
1
Order By: Relevance
“…These results are not surprising in light of the well-documented teratogenic effects of prenatal alcohol exposure on facial features [21,26,34]. Prenatal marijuana and tobacco exposure were also related to higher rates of physical abnormalities, findings also supported by previous research [1,10,27].…”
Section: Discussionsupporting
confidence: 85%
“…These results are not surprising in light of the well-documented teratogenic effects of prenatal alcohol exposure on facial features [21,26,34]. Prenatal marijuana and tobacco exposure were also related to higher rates of physical abnormalities, findings also supported by previous research [1,10,27].…”
Section: Discussionsupporting
confidence: 85%
“…Although total absence of this brain structure is rare, occurring at a rate of 0.1% in the typical population and 2% in the developmentally disabled (Jeret et al, 1986), a higher rate of ACC has been reported in individuals with FAS (Riley, et al, 1995;Swayze et al 1997). Also, ACC is commonly accompanied by ventricular abnormalities, as midline structures typically adjoining the corpus callosum are displaced (Johnson et al, 1996). While ACC is rare even among individuals with FAS, hypoplasia of the corpus callosum has been frequently reported (Autti-Ramo et al, 2002;Mattson et al, 1992;Riley et al, 1995;Sowell et al 2001b;Swayze et al, 1997).…”
Section: Corpus Callosummentioning
confidence: 54%
“…Fetal alcohol exposure causes Fetal Alcohol Spectrum Disorders (FASD), which have an estimated prevalence reaching 1% in North America (1). FASD are associated with defects to numerous organs, including the central nervous system (2). Defects to the central nervous system are especially diffuse and can include disruptions to the corpus callosum (3,4).…”
mentioning
confidence: 70%